Ответы и объяснения

2014-01-14T00:30:05+04:00
(a^{ \frac{1}{4} } + b^{ \frac{1}{4} } ) : ( \frac{b}{a^{ \frac{3}{4}} } + \frac{b ^{\frac{5}{4}} }{a})=(a^{ \frac{1}{4} } + b^{ \frac{1}{4} } ) :  \frac{b*a^{\frac14}+b ^{\frac{5}{4} }}{a}=(a^{ \frac{1}{4} } + b^{ \frac{1}{4} } ) :  \frac{b(a^{\frac14}+b ^{\frac{1}{4} })}{a}=\\
\\
(a^{ \frac{1}{4} } + b^{ \frac{1}{4} } ) *  \frac{a}{b(a^{\frac14}+b ^{\frac{1}{4} })}=\frac{a}{b}\\
\\
\frac{a}{b}=\frac{68}4=17
не совсем понятно начало решения во 2й скобке